Addressing landscape conservation and community development through national park boundary - Wang Qi; Zhong Linsheng; Yu Hu (Global Ecology and Conservation, 2025)
In the strategic expansion of protected areas, it is imperative to address sustainable development challenges by exploring innovative approaches to harmonize the conservation and utilization of ecological resources and landscape. Particularly, geological landscape category of national parks （GLNPs）in developing countries possess not only aesthetic value but also serve as productive resources that foster community prosperity. Adhering to the fundamental principles of protecting the authenticity and integrity of the landscape ecological system, this study proposes a novel methodology for delineating the national park (NP) boundary to balance the relationship between the landscape ecological resources protection and community development under the technical framework. We have delineated three national park schemes in Zanda Tulin, covering areas of 4597.04 km², 8109.28 km², and 4594.08 km², respectively. We propose the concept of a ''synergistic zone'' and argue that，considering the effective supply of agricultural production space and the uncertain impacts of future climate change on landscape resources, the 'one park, two zones, and three lines' model can effectively address these challenges.